Understanding the Values of Civility: A Review of Educational Literature Through Five Analytical Lenses - Ouladhadda, Aziz; Azhar, Adil (International Journal of Linguistics and Translation Studies, 2025)
This literature review explores the concept of school civility with the aim of making existing international research accessible and relevant to Moroccan researchers and educators. The paper begins by examining how civility has been defined across disciplines and identifies its core components and educational functions. Drawing on peer-reviewed studies retrieved from reputable databases such as Scopus, Web of Science, Springer, JSTOR, and Science Direct, the review categorizes the literature into five thematic areas: (1) pedagogical strategies for teaching values, (2) the role of teacher training programs in values education, (3) the presence of civility in English as a Foreign Language (EFL) teaching materials, (4) students’ and teachers’ perceptions of civil and uncivil behaviors, and (5) contextual factors correlated with school incivility. The findings suggest that while various interventions and strategies have been proposed and tested globally, there remain significant gaps in values education, particularly within teacher training programs and EFL curricula. The review concludes by identifying areas that warrant empirical investigation in the Moroccan context, offering a framework for future research on promoting civility in schools.